Effect of Allelopathy Reed Extract (Imperata Cylindrica) in The Growth of Stem and Flowers Of Cawit Chicken Plant (Capsicum Annuum L) - Eka Dyah Rahmawati, Nira (Jurnal Global Ilmiah, 2024)
Allelopathy is a phenomenon in which chemical compounds produced by plants can inhibit the growth of other plants around them. Cogongrass (Imperata cylindrica) is known as one of the plants that can produce allelopathic compounds that have a negative impact on the growth of other plants. This study aims to determine the effect of cogongrass extract on the growth of chili plants (Capsicum annuum L.), focusing on plant height and number of leaves. The study was conducted with an experimental design using a descriptive method. Cogongrass extract was tested at two concentrations: 1:2 (100 ml of extract and 200 ml of water) and 2:1 (200 ml of extract and 100 ml of water), as well as a control (without extract). Observations were made for three weeks. The results showed that cogongrass extract inhibited the growth of chili plants. The highest average plant height was achieved in the control treatment with 1,423.7 cm, while the 1:2 treatment produced an average height of 1,335 cm. The highest number of leaves was in the control with 604 leaves, while the 1:2 treatment produced 458 leaves. Cogongrass extract significantly inhibited the growth of chili plants, with a concentration of 1:2 being the most effective in reducing plant height and number of leaves. This study shows the potential of cogongrass extract as an inhibitory agent for the growth of other plants.